1993
DOI: 10.1002/j.1551-8833.1993.tb06031.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Iron Corrosion and the Disinfection of Biofilm Bacteria

Abstract: Previous research has shown a relationship between corrosion of an iron pipe and the protection of biofilm bacteria from disinfection. It is believed that the corrosion product reacts with chlorine disinfectants and prevents the biocide from penetrating the biofilm layer and inactivating the attached bacteria. The results of the current study show that even low levels of corrosion, i.e., <1 mpy, could interfere with free chlorine disinfection. High corrosion rates affected monochloramine disinfection. The rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
102
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 18 publications
4
102
0
1
Order By: Relevance
“…4 also illustrate that biofilms can rapidly form even in the presence of a 1-to 2-mg/liter free chlorine residual. Corrosion products have been previously shown to provide increased protection from free chlorine disinfection (19). cPVC pipe surfaces were incorporated into the pilot system, in part, to study disinfection efficiencies in the absence of corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…4 also illustrate that biofilms can rapidly form even in the presence of a 1-to 2-mg/liter free chlorine residual. Corrosion products have been previously shown to provide increased protection from free chlorine disinfection (19). cPVC pipe surfaces were incorporated into the pilot system, in part, to study disinfection efficiencies in the absence of corrosion.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of biofilm may cause many public health issues, such as protecting and supporting pathogenic microorganisms (Buswell et al, 1998), bacterial regrowth (LeChevallier et al, 1991), depletion of disinfection agents (Regan et al, 2002) and microbial corrosion (Holden et al, 1995;LeChevallier et al, 1993). Thus, the DS biofilm has received more concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In water distribution systems, the free chlorine residual level in excess of 0.2 mg/L should be maintained to reduce further microbial contamination (Al-Jasser, 2007). Several studies indicated possible negative effects of disinfections particularly on biofilm bacteria due to corrosion of metal pipe lines (LeChevallier et al, 1993). Since most of the old water distribution systems in cities particularly in developing countries are made up of iron pipelines, this has to be considered very seriously.…”
Section: Introductionmentioning
confidence: 99%